Implementation of Cooperative Learning Treffinger Type to Improve the Understanding of Class VI Students - Yullia Susilaningtyas; M. Bahri Musthofa (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This study aims to determine the application of the Treffinger learning model to improve the understanding of sixth-grade students. This research is a Classroom Action Research (CAR) with Kurt Lewin's model. The findings showed that the result of teacher observations in the first cycle was 72.2%, an increase to 91.6% in the second cycle. This increase also occurred in the observation of student activity in the first cycle, namely 68.75%, up to 90.62% in the second cycle. Increasing the learning process has an impact on increasing students' understanding of the natural and social appearance material of neighbouring countries. This can be seen from the increase in the average score of students in the first cycle from 74.76 to 82.80 in the second cycle which was classically complete. Likewise, student learning completeness in the first cycle was 65.38% to 92.30% in the second cycle with a good category.